Performance of different varieties/hybrids of black pepper (Piper nigrum L.) as mixed crop in coconut garden - Maheswarappa, H.P.; Krishnakumar, V.; Srinivasa Reddy, D.V.; Dhanapal, R.; Zachariah, T. John (Journal of Plantation Crops, 2012)
A field experiment was conducted at Central Plantation Crops Research Institute, Kasaragod during 2001 to 2010 for studying the performance of black pepper varieties/hybrids when grown as mixed crop in 36 years old WCT coconut garden. Varieties such as Panniyur-1, Panniyur-2, Panniyur-3, Panniyur-4, Panniyur-5, Sreekara, Subhakara, Panchami, Kottanadan, OPKM, Collection 1041(Thevam) and hybrids such as HP-780, HP-105, HP-1411, HP-813 and HP-34 were grown in three replications. Among the varieties, Thevam, Panniyur- 4, Panniyur- 5, Sreekara, Subhakara and Panchami produced higher number of laterals with more spread (at five years age) compared to the other varieties. Thevam recorded significantly higher number of spikes (202.5), whereas the lowest was recorded in HP 780 (21.5). The spike length was the highest in Panniyur- 5 (15.4 cm), but was on par with varieties such as Panniyur-1, Panniyur-2, HP-1411 and OPKM. Sreekara recorded the lowest spike length of 8.7 cm. Six years mean dry spike yield indicated that, the yield was significantly higher with Thevam (1.81 kg/vine) followed by Panniyur- 5, which had recorded a yield of 1.12 kg/vine and differed significantly over other varieties. Panchami recorded higher oil (5.6 %) and oleoresin content (12.6%) and was on par with Panniyur-4, Kottanadan and OPKM. Due to the mixed cropping of black pepper in coconut garden an improvement in the coconut yield was noticed (132.2 nuts/palm/yr) during 2009-10 compared to the coconut monocrop (101.3 nuts/palm/yr) during 1999 to 2001.